G20, Social Science, Environmental Science, Economics, Econometrics and Finance Research Trend - Paisal Halim; Syamsiah Badruddin; Muhammad Ikhsan Setiawan; Abdul Talib Bon (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
The G20 is a multilateral cooperation forum consisting of 19 major countries and the European Union (EU) which has a middle to high income class, developing countries to developed countries. G20 members consist of countries from various regions of the world. United States, Canada, Mexico, Argentina, Brazil, United Kingdom, Germany, Italy, France, Russia, South Africa, Saudi Arabia, Turkey, China, Japan, South Korea, India, Indonesia, Australia and the European Union. In the G20 Indonesia became one of the 5 strongest economies in Asia Pacific, including: (1) China GDP 14.72 trillion US dollars (2020) Area 9.597 million km2 Population 1.402 billion people (2020) China's largest economy from manufacturing, services, and agriculture. SCOPUS.COM analyze search results, Social Science, Environmental Science, Economics, Econometrics and Finance 22,997 documents result since 1974 to 2022, all field article. So today in good trend of research and publication in Social Science, Environmental Science, Economics, Econometrics and Finance. Compare top 15 affiliations, dominant affiliations from China and Malaysia, the best 3 affiliations are Beijing Institute of Technology 318 documents; Xi'an Jiaotong University 227 documents and Southwestern University of Finance and Economics 211 documents. Still no Indonesia research institution in top 15 of the list. Compare top 15 affiliations, the best 3 countries are China, USA and UK. In ASIA and ASEAN, Indonesia under China, Pakistan and Malaysia. So this is real challenge for Indonesia research institution to expand their research in Social Science, Environmental Science, Economics, Econometrics and Finance, trend in 2010-nowadays